Giant prolactinoma presenting as a skull base tumor with erosion of the cervical vertebrae: pronounced responsiveness to dopamine agonist treatment. (2nd January 2015) - Bjerg, Mia L.; Rosendal, Frederikke; Nielsen, Edith; Ulhøi, Benedikte Palm; Jørgensen, Jens O. L.
Abstract: Giant prolactinomas are rare and usually associated with symptoms attributable to hypopituitarism and compression of juxtasellar structures such as the cranial nerves of the cavernous sinus and the optic chiasm. Occasionally, they masquerade as skull base tumors with atypical symptoms. We describe a patient who presented with a low-energy trauma in the neck region that led to the initial diagnosis of a large skull base tumor eroding the cervical vertebrae. After stabilizing surgery, the patient responded to dopamine agonist therapy with normalization of serum prolactin levels and pronounced reduction in tumor volume.